Neurorehabilitation in Disorders of Consciousness - Giacino, Joseph T.; Katz, Douglas I.; Whyte, John (Seminars in Neurology, 2013)
Survivors of severe acquired brain injury often experience prolonged disturbance in consciousness following emergence from coma. Most individuals pass through the vegetative or minimally conscious states en route to eventual recovery of consciousness, although either condition may be permanent. Rehabilitation clinicians charged with the care of these patients face numerous challenges as there are many open questions concerning diagnostic and prognostic accuracy, the natural history of recovery, and the most effective approaches to prevent medical complications and facilitate functional recovery. The last 5 years have been witness to a marked increase in well-designed empirical investigations concerning the rehabilitation of patients with disorders of consciousness. In this article, the authors review recent evidence concerning key factors that influence the course of recovery, present a model of care designed to mitigate medical complications, describe a systematic approach to assessment, and review the effectiveness of treatment interventions utilized in the rehabilitation setting.
Keywords: disorders of consciousness; vegetative state; minimally conscious state; rehabilitation; outcome